NF‐κB is crucial in proximal T‐cell signaling for calcium influx and NFAT activation. Issue 12 (22nd October 2014) - Bronk, Crystina C.; Yoder, Sean; Hopewell, Emily L.; Yang, Shengyu; Celis, Esteban; Yu, Xue‐Zhong; Beg, Amer A.
Abstract : In the accepted model of T‐cell activation, parallel signal‐transduction pathways activate the transcription factors NF‐κB, NFAT, and AP‐1 to drive clonal expansion of T cells in response to Ag. Genome‐wide transcriptional profiling following Ag‐induced CD8 + T‐cell activation in C57BL/6 mouse T cells revealed that genes regulated by NFAT were also reduced in the absence of NF‐κB p50 and cRel subunits. Importantly, p50 −/− cRel −/− CD8 + T cells had significantly diminished NFAT and AP‐1 activation compared with WT or PKCθ −/− CD8 + T cells. Attenuated NFAT activation after TCR engagement was associated with reduced calcium influx, PLCγ and Zap70 activation. Interestingly, pharmacological bypass of PLCγ‐regulated pathways largely rescued p50 −/− cRel −/− T‐cell proliferative defects. These results indicate a crucial and unexpected requirement for NF‐κB p50 and cRel subunits in proximal TCR signaling and calcium responses. They further suggest that key defects in T cells in the absence of NF‐κB pathway components may be due to impaired proximal T‐cell signaling.